Graspables revisited: multi-touch vs. tangible input for tabletop displays in acquisition and manipulation tasks - Tuddenham, Philip; Kirk, David; Izadi, Shahram (Proceedings of the 28th international conference on Human factors in computing systems, 2010)
We present an experimental comparison of multi-touch and tangible user interfaces for basic interface actions. Twelve participants completed manipulation and acquisition tasks on an interactive surface in each of three conditions: tangible user interface; multi-touch; and mouse and puck. We found that interface control objects in the tangible condition were easiest to acquire and, once acquired, were easier/more accurate to manipulate. Further qualitative analysis suggested that in the evaluated tasks tangibles offer greater adaptability of control and specifically highlighted a problem of exit error that can undermine fine-grained control in multi-touch interactions. We discuss the implications of these findings for interface design.